Assessing Sample Bias among Venue-Based Respondents at Medical Marijuana Dispensaries. Issue 1 (1st January 2016) - Thomas, Crystal; Freisthler, Bridget
ABSTRACT: Venue-based sampling is the identification of, and outreach to, locations visited by the population of interest for the purpose of collecting data. The method is frequently used to reach specific populations, commonly referred to as "hidden populations." Medical marijuana users represent a hidden population of persons who use marijuana for medicinal purposes. We examine whether venue-based procedures introduce selection or non-respondent bias into the study. The venue based sampling procedures employed for the UCLA Medical Marijuana Study used a two-stage, venue-based sampling approach. First, analyses were conducted to assess potential bias within dispensaries that agreed to participate in the surveys. Secondly, analyses were conducted to examine differences among patrons who responded to surveys. Overall, selection bias was generally absent among study results. Results also illuminated the minimal respondent bias observed among the survey respondents. Results suggest that the use of dispensaries to access and survey medical marijuana users is a viable option to gather patient information that adequately represents the greater population of medical marijuana users in Los Angeles. Thus, recommendations and conclusions based on findings from venue-based studies of medical marijuana users at dispensary sites serve to impartially inform meaningful research.